A CURRENT NEED FOR MODERN INSTRUMENTS IN FORENSIC PATHOLOGY: A WAY FORWARD - Paranitharan, P.; Hulathduwa, S.R. (Sri Lanka Journal of Forensic Medicine, Science & Law, 2016)
Attached

Routine dissection of the cadaver followed by mandatory and ancillary investigations is still the most widely used method in forensic autopsy throughout the globe. In contrast to most other disciplines of medicine, instruments used in routine autopsy work remain plain, simple, unsophisticated and virtually unchanged for over a century. Incorporation of modern technology to improve these instruments to meet the new challenges such as minimizing the risk of biohazards, acquisition of precision in dissection, facilities for simultaneous imaging, sampling and archiving the information and finally making the dissection a less cumbersome a task with lesser degree of dependability on individual human skills has become the need of the day. The authors briefly discuss few initiative steps taken along this long pathway
Keywords: forensic pathology; modern instruments; advanced techniques; human cadaver